Do all fractions of organic matter contribute equally in shale porosity? A case study from Upper Ordovician Utica Shale, southern Quebec, Canada. (April 2018) - Ardakani, Omid H.; Sanei, Hamed; Ghanizadeh, Amin; Lavoie, Denis; Chen, Zhuoheng; Clarkson, Christopher R.
Abstract: In many unconventional hydrocarbon systems, organic matter (OM) substantially contributes to total porosity of the rock that led to a positive correlation between total organic carbon (TOC) and porosity. While organic porosity is an important reservoir property of unconventional hydrocarbon systems, TOC of these rocks consists of different macerals or petrographic fractions. These TOC fractions can be geochemically divided and quantified by the revised, extended slow heating (ESH) Rock-Eval analysis. This study discusses the contribution of different fractions of OM on porosity variation in the mature to overmature Utica Shale in southern Quebec, using ESH Rock-Eval analysis, helium pycnometery, scanning electron microscopy (SEM), and X-ray diffraction (XRD) mineralogy. Selected samples from three wells at depths of ∼400, 700, and 2000 m, covering a range of thermal maturity from late peak oil window (VRoeqv. ∼1%) to dry gas zone (VRoeqv. ∼2.1%) were analyzed in this study. The predominant OM constituents are solid bitumen, chitinozoans, and minor graptolites with mean TOC of 1.1 ± 0.4 wt. %. The mean porosity for oil and gas window samples decreases with depth from 3.9 ± 0.9 to 2.6 ± 0.5%, respectively. The SEM images reveal that organic porosity is limited to pores developed in solid bitumen, while regardless of thermal maturity, chitinozoans have a non-porous structure throughout the oil to dry gas window. This observation suggests that the impact of thermal maturity on porosity is different for different OM fractions (i.e., macerals), leading to different contribution of OM fractions to total porosity. The latter conclusion is further supported by the improved correlation observed between the solid bitumen fraction and porosity compared to TOC-porosity correlation for oil window samples. Our entire data set suggests that OM (i.e., bitumen fraction), especially in the dry gas window, is not the major controlling factor on the total porosity in the Utica Shale, whereas, intergranular porosity has the dominant control on total porosity. This observation suggests that the hydrocarbon storage potential may largely reside in inorganic pores rather than organic pores in the analyzed intervals of the Utica Shale. The decrease in total porosity observed from shallower samples (i.e., oil window) to deeper samples (i.e., dry gas window) also suggests that intergranular porosity is the dominant porosity component, which decreases with burial. Highlights: The major pore types and their contribution to the Utica Shale total porosity is discussed. Chitinozoans as major constituents of TOC do not contribute to total porosity, while solid bitumen does. Regardless of thermal maturity, chitinozoans have a non-porous structure. Porosity appears to largely reside in inorganic pores rather than organic pores.